Factors Affecting Caesarean Labor in RSUD Lembang in 2017 - Regina A B Pratiwi; Rimonta F Gunanegara; July Ivone (Journal of Medicine and Health, 2019)
Indonesian Maternal Mortality Ratio (MMR) based on the Survei Demografi Kesehatan Indonesia (SDKI) in 2012 is 356/100.000 live birth whereas the target of Sustainable Development Goals (SDG’s 70/100,000 live birth by 2030. A decent labor assistance in both vaginal and sectio caesarean labor is necessary in reducing MMR. This study aimed to analyze the relationship between maternal age, parity and payment method with labor through caesarean section. This is an observational analytic study using cross sectional design. The data was obtained through secondary data from medical record. During 2017 there were 183 caesarean sections in RSUD Lembang as our research location. The data was analyzed univariately and bivariately by using Chi Square test (?=0.05). The results shows that factors associated with caesarean labor are maternal age (p=0.032; OR=4.617), parity (p=0.035; OR=4.442) and payment method (p=0.036; OR=4.417). It can be concluded that maternal age, parity and payment method affect caesarean labor. Keywords: caesarean labor, caesarean section, age, parity, payment method